EFFECT OF MICROWAVE IRRADIATION ON NUTRITIVE VALUE OF SUNFLOWER MEAL FOR RUMINANTS USING IN VITRO GAS PRODUCTION TECHNIQU - N. Maheri-Sis; A. R. Baradaran-Hasanzadeh; R. Salamatdoust; O. Khosravifar; A. Agajanzadeh-Golshani; J. Dolgari-Sharaf (Journal of Animal and Plant Sciences, 2011)
This study was conducted to estimate nutritive value of sunflower meal (SFM) and evaluate the effect of microwave irradiation on the metabolizable energy (ME), organic matter digestibility (OMD) and short chain fatty acids (SCFA) production of sunflower meal using in vitro gas production technique. Sunflower meal was exposed to 1000W microwave irradiation for six minutes. The sun flower meal sample(1g) were incubated with rumen liquor taken from three fistulated Ghezel rams at 2, 4, 6, 8, 12, 16, 24, 36 and 48 h. Cumulative gas production volume at 24 h incubation, for treated SFM was significantly (P< 0.001) higher than that of untreated SFM (171.48 vs. 154.44 ml). Microwave treated SFM also had significantly higher ME (8.97 vs. 8.43 Mj Kg-1DM), OMD (67.69 vs. 65.10 %) and SCFA (0.75 vs. 0.68 mmol) than control SFM (P< 0.001). Based on results of this study, it can be concluded that microwave irradiation may be a useful method to enhance nutritive value of sunflower meal.
Keywords: sunflower meal; microwave; nutritive value; gas production; metabolizable energy